1996
DOI: 10.1177/009127009603601107
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Tamsulosin Hydrochloride in Patients with Renal Impairment: Effects of α1‐Acid Glycoprotein

Abstract: The pharmacokinetics of tamsulosin hydrochloride in patients with renal impairment were compared with those in healthy volunteers, and the factors that influenced plasma levels of tamsulosin were elucidated. A single oral dose of 0.2 mg of tamsulosin was given and blood and urine samples were obtained for 36 hours after administration. Unbound plasma concentration of tamsulosin was measured by a combination of equilibrium dialysis and liquid chromatography tandem mass spectrometry methods to examine the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…31 Moreover, decreased CL oral and prolonged t 1 /2 were observed in patients with renal disease when the bound fraction of TAM was increased by elevation of plasma ␣ 1 -AGP level. 12 This study clearly demonstrates that increased protein binding exerts different influences on the pharmacokinetics of TAM in rats and humans because of the difference in magnitude of CL tot and Vd ss between the two species.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…31 Moreover, decreased CL oral and prolonged t 1 /2 were observed in patients with renal disease when the bound fraction of TAM was increased by elevation of plasma ␣ 1 -AGP level. 12 This study clearly demonstrates that increased protein binding exerts different influences on the pharmacokinetics of TAM in rats and humans because of the difference in magnitude of CL tot and Vd ss between the two species.…”
Section: Discussionmentioning
confidence: 74%
“…In fact, the plasma concentration of TAM in patients with renal disease was found to be significantly higher than in healthy subjects. 12 In that study, it is also suggested that an increase in plasma protein binding may affect the time-concentration profile of plasma unbound TAM because of a change in distribution of "free" TAM and a decrease in systemic clearance of "total" TAM. The unbound drug concentration should be a more appropriate indicator for evaluation of the drug's safety and efficacy than the total drug concentration because the unbound form is thought to be directly associated with pharmacologic effects.…”
Section: Introductionmentioning
confidence: 93%
“…The pharmacokinetics, efficacy and toxicology of basic drugs are influenced by the AAG variations in humans [2,6,11,12,[16][17][18][19]. Action is therefore required sometimes to change serum AAG levels before basic drugs are administered.…”
Section: Discussionmentioning
confidence: 99%
“…5, the maximum plasma unbound concentration of tamsulosin (4 h) after oral administration (slowrelease dosage form: 0.45 mmol) in healthy volunteers was 0.16 nM and the plasma unbound concentration 24 h later was 0.03 nM. 16) Similarly, the maximum plasma unbound concentration of terazosin after oral administration (2.2 mmol) was 9.51 nM and 24 h later it was 1.22 nM. 17) From these data, a 1 -adrenoceptor occupancy by both drugs in the human prostate was estimated using a 1 -adrenoceptor-binding affinities (K i for tamsulosinϭ0.04 nM, K i for terazosinϭ1.04 nM) in the human prostate.…”
Section: Adrenoceptor-binding Parameters In the Humanmentioning
confidence: 90%
“…10) Consequently, the prediction of prostatic a 1 -adrenoceptor occupancy in the present study suggests a relatively long duration of the clinical effects of silodosin in patients with BPH. Furthermore, based on K i values for competitive inhibition of human prostatic a 1 -adrenoceptor radioligand binding 5,18,19) and plasma unbound concentrations in healthy volunteers, 16,17) a 1 -adrenoceptor occupancy in the human prostate by tamsulosin and terazosin at clinical doses was estimated to be 70-90% 1-6 h after oral administration, and 40-50% even 24 h later. Thus it should be noted that, despite about two orders of differences in plasma unbound concentrations after clinically effective oral dosages of silodosin, tamsulosin and terazosin, there may be comparable magnitude of prostatic a 1 -adrenoceptor occupancy after oral administration of these drugs in humans.…”
Section: Adrenoceptor-binding Parameters In the Humanmentioning
confidence: 99%